Identificação do cidadão brasileiro em serviços digitais: dispensa de documentos digitalizados - Santos, Lucas Albertoni (2020)
With the evolution of technology, Brazilian financial institutions have started to digitize the citizens’ documents to replace the outdated physical copy method. However, it is currently still necessary for the customers to go to the financial institution in order to have their documents authenticated since there is no other electronic means that allows the institution to receive the digital citizens’ data completely and safely. This is disadvantageous for both the customer, who needs to visit the institution’s physical location, and for the company, who needs to provide service locations and employees for this purpose. In order to solve these problems, fintechs have been created, which are companies that use state-of-the-art technology to provide financial services with a better focus on the customer. Fintechs have started to receive documents digitally in order to eliminate the necessity of citizens’ having to go personally to the institution’s physical location. However, there is still some need for collaborators to carry out the analysis of the document received by the citizen. Given this scenario, the paper asks the following questions. Is it necessary that the company receive the documents from the citizen personally? Is it possible to develop a solution that performs the identification and authentication of citizens’ documents in a secure and entirely digital way? As a solution, the present dissertation presents the examples of the services that the companies Google and Facebook are offering to companies for the authentication of their customers. It proposes that such forms of identification and authentication should also be made available by the Brazilian government. For the sake of comparability, this dissertation presents the concept of electronic government or e-gov used by the Estonian government, which is a world reference in electronic services. It then compares it with the electronic services that the Brazilian government is presently making available to its citizens through its websites. Furthermore, authentication concepts are addressed with the three commonly known questions in the document authentication process. In order to validate the proposed solutions for the form of identification and authentication provided by the Brazilian government in compliance with standards of Citizen Science and in a safe way for companies, definitions of implementations are made that have been ben followed by the services analyzed in Estonia along with the respective concepts authentication. Next, a flow chart of the current processes is designed. In a new chart, a form of integration between the systems of the existing agencies is proposed to design a horizontally scalable solution of great use to Brazil. For the design of this solution, a division is made in three stages: (1) “centralized data”, (2) “national authenticator”, and (3) “solution of the visual form” to finally achieve a solution that responds to questions posed above. Finally, the functionalities are described, developed, and tested by means of case studies and practices such as TDD and BDD. Integrated laboratory test cases are also presented to demonstrate and exemplify the operability of the proposed measures